Willingness to pay for primary health care at public facilities in the Western Cape Province, Cape Town, South Africa. (1st January 2021) - Chiwire, P.; Evers, S. M.; Mahomed, H.; Hiligsmann, M.
Abstract: Background and objectives: As facilities are being prepared for the implementation of National Health Insurance (NHI) in South Africa, there is a pressing need to understand how the public equates the provision of health services at Primary Health Care (PHC) centres with monetary value. Accordingly, this exploratory study was designed to ascertain the willingness to pay (WTP) for public primary healthcare services in South Africa and to identify factors that influence the WTP. Methods: The study was conducted in Cape Town, South Africa, among 453 persons presenting at two public primary health care centres, namely Bothasig Community Day Centre (CDC) and Goodwood CDC. The study used the contingent valuation range methodology. Descriptive statistics, multiple logistic and tobit regression analyses were conducted to assess demographics, socio-economic, and health access factors that influence WTP. Results: Overall, 60% of participants were willing to pay for services offered at the PHC facilities. The average willingness to pay for all participants was 49.44 ZAR, with a median of 25 ZAR. The multiple logistic regression for grouped facilities showed unemployment, public transport, and the facility attended to be significant while public transport, facility visits, and facility attended were the only significant variables in the tobit model. There was less willingness to pay for those unemployed in comparison with students, those using public transport rather than walking, those frequenting the facilities more than first-time visitors and those attending Goodwood facility in comparison with Bothasig. Conclusion: This study revealed factors related to the participants' WTP and to their willingness to contribute towards the health service, though at very low amounts. Understanding the economic value placed upon a service provided in a facility is essential in decision-making for quality care improvements, especially as the South African health system is making the facilities ready for NHI.